PENGARUH PAJAK TANGGUHAN, PERENCANAAN PAJAK, DAN LEVERAGE TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2016) - Franky Afrizal; Amir Hasan Amir Hasan; Nur Azlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to examine the effects of deferred taxes, tax planning and leverage on earnings management at manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2014-2016. The sample in this study consists of 41 manufacturing companies listed on the IDX (Indonesia Stock Exchange) during the period 2014-2016 selected based on certain criteria by using purposive sampling. With the observation period for 3 years then the sample of the study amounted to 123 samples. The analysis method used is multiple linear regression analysis and coefficient of determination processed using SPSS program. The result of multiple linear regression test proves that deferred tax assets, tax planning and leverage have positive and significant effect to earnings management. While the deferred tax burden has no effect on earnings management. The result of determination coefficient test (Adjusted R²) shows that 42.2% of the variation of earnings management can be explained by independent variable, while the remaining 64,9% is explained by other variable which is not in this research.Keywords: earnings management, deferred tax, tax planning, leverage